Folklore and popular tradition in Polish literature of romanticism - Matayaszczyk Grenda, Agnieszka (Eslavística Complutense, 2013)
Polish Romantic writers and researchers collected folk traditions and motifs; they published this research in journals of culture and ethnography. Popular songs and legends that were never before included in the national culture, once considered products of the imagination of the uneducated and superstitious people, forever gained their place in national literature.